The effect of midsole hardness of running shoe on fatigue of lower extremity muscles and impact force - Kim, E.; Lim, K.; Cho, S.; Lee, K. (Korean Journal of Sport Biomechanics, 2019)
Objective: The aim of this study was to investigate the effect of midsole hardness of running shoe on muscle fatigue and impact force during distance running. Method: Ten healthy college recreational runners who were performing distance running at least three times a week participated in this experiment. They were asked to run for 15 minutes in the treadmill at 10 km/h with running shoes having three different types of midsole hardness (Soft, Medium, Hard). EMG signal and insole pressure were collected during the first and last one minute for each running trials. Data were analyzed using a one-way analysis of variance (ANOVA) with repeated measures. Results: Midsole hardness did not affect the consistency of stride length. For the median frequency of the EMG signal, only VL was affected by midsole hardness; that of medium was greater than other midsoles (p<.05). The loading rate of impact forces increased by midsole hardness (p<.01). Conclusion: Although soft midsole could attenuate impact forces at heel contact, it might have a negative effect on the fatigue of muscle which could decelerate the body after heel contact. Therefore, it is necessary to select the optimum hardness of midsole carefully for both reduction impact forces and muscle fatigue.